Metropolitan Revolution or Metropolitan Evolution? The (Dis)continuities in Metropolitan Institutional Reforms. - Tomàs, Mariona (Springer, 2020)
The development and change of metropolitan institutions have been at the heart of political and theoretical debates for decades. However, given the widespread path dependency of institutional development, we may ask what has really changed over time? The aim of this chapter is to evaluate recent institutional developments that have come to be seen as emblematic of a ‘metropolitan revolution’ in governance. Based on the description of current and the past developments, the chapter will question the nomenclature of institutional ideas on metropolitan governance that is also often used to distinguish different periods if not paradigms of metropolitan governance. Our focus - though not exclusively - will be on developments in Europe where we will analyse recent reforms to reveal how allegedly broad, universal trends and phases of metropolitan institutional reform are, in fact, occurring at different paces, in different ways, at different times, and with different degrees of institutionalisation across space. The chapter concludes with the assertion that current processes of change pertaining to metropolitan institutions are actually part of an evolution rather than of a revolution.
Keywords: Metropolregion; Institutionalisierung; Regionstyp; Entwicklungsdynamik; Regional Governance; Planungsinstitution; Veränderung; Planungskompetenz; Kompetenzabgrenzung; Finanzierung; Legitimation